Liability of Police Officers for Misuse of Their Weapons - Greenston, Herbert E. (1967)
The focus of this article is twofold: it will begin by examining the historical development of the body of law which deals with the liability of the police officer for the negligent use of his weapons, and it will attempt to consider the practical problems confronting the attorney for the injured plaintiff in marshalling his evidence and presenting his case